2017
DOI: 10.1002/maco.201709478
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion properties of bioresorbable FeMn‐Ag alloys prepared by selective laser melting

Abstract: FeMn‐Ag alloys as potential bioresorbable implant materials were prepared by selective laser melting (SLM) from mixed powders of FeMn and Ag. The microstructure of the samples is characterized by presence of few micrometers to several tens of micrometer large Ag‐phases within the FeMn matrix. The microstructure dependent corrosion and biomineralization processes in simulated body fluid (SBF) were studied in‐situ by means of electrochemical impedance spectroscopy (EIS). The microstructure and local surface film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
5
35
1
Order By: Relevance
“…Liu et al [15] developed a Fe-30Mn-1Ag alloy using a rapid solidification technique and found that the alloy corroded faster in simulated body fluid due to the microgalvanic effect of the Ag-rich particles with the Fe-Mn matrix. Similar microgalvanic effect of silver addition to accelerating corrosion was observed by Wiesner et al [16] on Fe-Mn-Ag alloys prepared by selective laser melting from mixed powders of Fe-Mn and Ag. However, at longer immersion period, they observed the formation of oxide/phosphate-based corrosion layer that inhibited the microgalvanic effect to…”
Section: Introductionsupporting
confidence: 81%
“…Liu et al [15] developed a Fe-30Mn-1Ag alloy using a rapid solidification technique and found that the alloy corroded faster in simulated body fluid due to the microgalvanic effect of the Ag-rich particles with the Fe-Mn matrix. Similar microgalvanic effect of silver addition to accelerating corrosion was observed by Wiesner et al [16] on Fe-Mn-Ag alloys prepared by selective laser melting from mixed powders of Fe-Mn and Ag. However, at longer immersion period, they observed the formation of oxide/phosphate-based corrosion layer that inhibited the microgalvanic effect to…”
Section: Introductionsupporting
confidence: 81%
“…The tabulation of such studies are presented in Table 4. 61,64,[73][74][75][76][77]80,[82][83]86,[95][96][97][98][99][100][101][102][103][104] Environments containing chloride ions are well known to be detrimental to the durability of stainless steels, with a number of studies tabulated above appropriately focusing on such electrolytes. 105 In a study by Ganesh, et al, 95 two batches of specimens (termed "A" and "B") were produced via DLD, by utilizing similar parameters to produce Type 316L specimens.…”
Section: Ferrous Alloysmentioning
confidence: 99%
“…The corrosion of SLM FeMn-Ag was investigated by Wiesener, et al, 104 in SBF. The interaction of Ag precipitates and FeMn matrix created a galvanic couple in the early stages of immersion in SBF.…”
Section: Crackmentioning
confidence: 99%
“…[304] Lately, the focus shifted from the predominantly investigated Ti6Al4V alloy toward alternative titanium based alloys, such as TiTa or TiTaZr, which have an advantage regarding their Young's modulus, which is much lower and thus, reduces stressshielding effects. [305,306] An overview about important investigations of the utilization of AM in the medical sector is provided in Table 32. Recent studies showcased their successful fabrication via AM, in particular pure magnesium and FeMnAg.…”
Section: Am In the Medical Sectormentioning
confidence: 99%